Effect of adding Nanoclay (Cloisite-30B) on the Proton Conductivity of Sulfonated Polybenzimidazole - Hashem Ahmadizadegan (Nanochemistry Research, 2017)
A novel sulfonated polybenzimidazole/organoclay (Cloisite-30B) (SPBI/clay) nanocomposite membranes was successfully synthesized based on aromatic diacide (1) and diaminobenzidine. Nanocomposite membranes were fabricated using 1, 4-bis (hydroxymethyl) benzene (BHMB) as cross-linker, and Cloisite-30B organoclay as the pseudo cross-linker. The cross-linked SPBI/clay nanocomposite membranes were prepared via solution intercalation method. Participation of reactive organoclay in the cross-linking process was established from ion exchange capacity (IEC) measurements and FTIR studies. Wide angle X-ray diffraction (WAXD), field emission-scanning electron microscopy (FE-SEM), and transmission electron microscopy (TEM) techniques confirmed the presence of a combination of the intercalated and partially exfoliated clay conﬁrmed mixed clay dispersion morphology of intercalation and partial exfoliation of the clay platelets in the cross-linked SPBI/clay nanocomposite membrane. The cross-linked SPBI/clay nanocomposite membranes showed higher tensile strength, modulus and lower elongation at break compared to neat cross-linked SPBI. Water and methanol uptake studies revealed superior barrier properties of cross-linked SPBI/clay nanocomposite membranes compared to cross-linked SPBI. Furthermore, thermal stability, residual solvent in the membrane film, and structural ruination of membranes were analyzed by thermal gravimetric analysis (TGA). TGA data indicated an increase in thermal stability of the SPBI/clay nanocomposite membranes in compared to the pure polymer. The oxidative stability of SPBI improved remarkably with cross-linking and subsequent clay addition. These improvements in the thermo-mechanical, barrier and oxidative stability of the membranes could be achieved without signiﬁcantly affecting the protonic conductivity.